Réponses

2013-12-23T15:57:32+01:00
A=(x+1)²+(x-3)²
A=x²+2x+1+x²-6x+9
A=2x²-4x+10

B=(3-x)²+(x+5)²
B=9-6x+x²+x²+10x+25
B=2x²+4x+34

C=(x-2)²+(x+4)(x-4)
C=x²-4x+4+x²-4x+4x-16
C=2x²-4x-12

D=(x+1)(x-1)+(x+4)²
D=x²-x+x-1+x²+8x+16
D=2x²+8x+15

E=(x-5)²+(2x+7)(2x-7)
E=x²-10x+25+4x²-14x+14x-49
E=5x²-10x-24
2013-12-23T16:03:53+01:00
Exercice 1 B2 : Développer et réduire :

A = (x + 1)² + (x - 3)²
A = x² + 2x + 1 + x² - 6x + 9
A = 2x² - 4x + 10

B = (3 - x)² + (x + 5)²
B = 9 - 6x + x² + x² +10x + 25
B = 2x² + 4x + 34

C = (x - 2)² + (x + 4) (x - 4)
C = x² - 4x + 4 + x² - 4x + 4x- 16
C = 2x² - 4x -12

D = (x + 1) (x - 1) + (x + 4)²
D = x² - x + x - 1 + x² + 8x + 16
D = 2x² + 8x +15

E = (x - 5)² + (2x + 7) (2x - 7)
E = x² - 10x + 25 + 4x² - 14x +14x - 49
E = 5x² - 10x - 24